A combined fragment-based virtual screening and STD-NMR approach for the identification of E-cadherin ligands - Vasile, Francesca; Lavore, Francesca; Gazzola, Silvia; Vettraino, Chiara; Parisini, Emilio; Piarulli, Umberto; Belvisi, Laura; Civera, Monica (Frontiers in Chemistry, 2022)
Cadherins promote cell-cell adhesion by forming homophilic interactions via their N-terminal extracellular domains. Hence, they have broad-ranging physiological effects on tissue organization and homeostasis. When dysregulated, cadherins contribute to different aspects of cancer progression and metastasis; therefore, targeting the cadherin adhesive interface with small-molecule antagonists is expected to have potential therapeutic and diagnostic value. Here, we used molecular docking simulations to evaluate the propensity of three different libraries of commercially available drug-like fragments (nearly 18,000 compounds) to accommodate into the Trp2 binding pocket of E-cadherin, a crucial site for the orchestration of the protein’s dimerization mechanism. Top-ranked fragments featuring five different aromatic chemotypes were expanded by means of a similarity search on PubChem database (Tanimoto index > 90%). Of this set, seven fragments containing an aromatic scaffold linked to an aliphatic chain bearing at least one amine group were finally selected for further analysis. Ligand-based NMR data (Saturation Transfer Difference, STD) and molecular dynamics simulations suggest that these fragments can bind E-cadherin mostly through their aromatic moiety, while their aliphatic portions may also diversely engage with mobile regions of the binding site. A tetrahydro--carboline scaffold functionalized with an ethylamine emerged as the most promising fragment.